Increased RyR2 open probability induces neuronal hyperactivity and memory loss with or without Alzheimer's disease–causing gene mutations. Issue 11 (5th January 2022) - Yao, Jinjing; Liu, Yajing; Sun, Bo; Zhan, Xiaoqin; Estillore, John Paul; Turner, Ray W.; Chen, S. R. Wayne
Abstract: Introduction: Neuronal hyperactivity is an early neuronal defect commonly observed in familial and sporadic Alzheimer's disease (AD), but the underlying mechanisms are unclear. Methods: We employed a ryanodine receptor 2 (RyR2) mutant mouse model harboring the R4496C +/– mutation that markedly increases the channel's open probability (Po) to determine the impact of increased RyR2 activity in neuronal function without AD gene mutations. Results: Genetically increasing RyR2 Po induced neuronal hyperactivity in vivo in anesthetized and awake mice. Increased RyR2 Po induced hyperactive behaviors, impaired learning and memory, defective dendritic spines, and neuronal cell death. Increased RyR2 Po exacerbated the onset of neuronal hyperexcitability and learning and memory impairments in 5xFAD mice. Discussion: Increased RyR2 Po exacerbates the onset of familial AD–associated neuronal dysfunction, and induces AD‐like defects in the absence of AD‐causing gene mutations, suggesting that RyR2‐associated neuronal hyperactivity represents a common target for combating AD with or without AD gene mutations.